The first-line antituberculosis drugs, and their fixed-dose combination induced abnormal sperm morphology and histological lesions in the testicular cells of male mice - Bakare, Adekunle A.; Moses, Victoria Y.; Beckely, Charles T.; Oluyemi, Toluwani I.; Ogunfeitimi, Gift O.; Adelaja, Aduragbemi A.; Ayorinde, Glory T.; Gbadebo, Adeyinka M.; Fagbenro, Olukunle S.; Ogunsuyi, Olusegun I.; Ogunsuyi, Opeoluwa M.; Ige, Olusoji Mayowa (Frontiers in Cell and Developmental Biology, 2022)
Rifampicin (RIF), Isoniazid (INH), Ethambutol (EMB), Pyrazinamide (PZA), and/or their fixed-dose combination (FDC) are extensively prescribed in the cure of Tuberculosis (TB) globally. In spite of the beneficial effect, these drugs are capable of inducing cellular toxicity. Existing information on the genotoxic effects of the first-line anti-TB drugs is limited and contentious. Herein, we evaluated the reproductive genotoxicity of RIF, INH, EMB, PZA, and their FDC utilizing the mouse sperm morphology assay. Histological examination of the testes of exposed mice was also performed. Male Swiss albino mice (11–13 weeks old) were intraperitoneally exposed for 5 consecutive days to each of the anti-TB drugs at four different doses of 6.25, 12.5, 25, and 50 mg/kg bw of PZA; 2.5, 5.0, 10, and 20 mg/kg bw of RIF; 1.25, 2.5, 5.0 and 10 mg/kg bw of INH; 3.75, 7.5, 15 and 30 mg/kg bw of EMB; and 7, 14, 28 and 56 mg/kg bw of FDC corresponding respectively to ×0.25, ×0.5, ×1 and ×2.0 of the standard daily dose. In comparison with the negative control (normal saline), there was no significant difference in the testicular weight and organo-somatic index of exposed mice. There was an increase (p > 0.05) in the frequency of abnormal spermatozoa at most of the tested doses of each drug and a dose-dependent decrease with the FDC. Each of the anti-TB drugs except the FDC induced pathological lesions in the testes. These findings suggest that the individual first-line anti-TB drug unlike the FDC has the potential to provoke testicular anomalies in male mice.